Production of anhydrous ethanol using oil palm empty fruit bunch in a pilot plant - Jeon, Hyungjin; Kang, Kyeong-Eop; Jeong, Jun-Seong; Gong, Gyeongtaek; Choi, Jae-Wook; Abimanyu, Haznan; Ahn, Byoung Sung; Suh, Dong-Jin; Choi, Gi-Wook (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Bioethanol production from lignocellulosic biomass for use as an alternative energy resource has attracted increasing interest, but short-term commercialization will require several technologies such as low cost feedstock. The huge amount of oil palm empty fruit bunches (EFB) generated from palm oil industries can be used as a raw material for cheap, renewable feedstock for further commercial exploitation. Using a pilot-scale bioethanol plant, this study investigated the possibility of utilizing oil palm empty fruit bunches as a renewable resource. All bioethanol production processes such as pretreatment, hydrolysis, fermentation, and purification were constructed as automatically controlled integrated processes. The mass balance was calculated from operational results. Changhae ethanol multiexplosion pretreatment with sodium hydroxide was conducted to improve the enzymatic hydrolysis process, and a separate hydrolysis and fermentation process was used for producing bioethanol at an 83.6% ethanol conversion rate. In order to purify the ethanol, a distillation and dehydration facility was operated. Distillation and dehydration efficiencies were 98.9% and 99.2%, respectively. The material balance could be calculated using results obtained from the operation of the pilot-scale bioethanol plant. As a result, it was possible to produce 144.4 kg anhydrous ethanol (99.7 wt%) from 1000 kg EFB. This result constitutes a significant contribution to the feasibility of bioethanol production from lignocellulosic biomass and justifies the pilot plant's scale-up to a commercial-scale plant. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DILUTE-ACID PRETREATMENT; BIOETHANOL PRODUCTION; ENZYMATIC-HYDROLYSIS; BIOMASS